Kemampuan Guru Menyusun IAI untuk Pembelajaran Matematika Berdiferensiasi melalui Kurikulum Merdeka di SD - Friansah, Drajat; Nugroho, Khathibul Umam Zaid; Yanto, Yufitri (STIE Amkop Makassar, Indonesia, 2023)
This service aims to improve elementary school teachers' ability to develop initial assessment instruments (IAI) for differentiated mathematics learning through the Merdeka curriculum in elementary schools. This service was given to teachers at SD Negeri 2 Muara Beliti, Lubuklinggau, Indonesia. Training is carried out using hybrid learning. The result of this service was that 95% of teachers responded very positively and liked this workshop and only 1 (one) participant said it was normal. Participants improved their abilities in compiling and applying IAI. The conclusion is that the workshop using the Peer Assisted Learning Strategies (PALS) method in differentiated learning concluded that it could improve the ability of SD Negeri 2 Muara Beliti teachers to compile and implement IAI through differentiated learning in the independent curriculum.